Intracardiac extension of intravenous leiomyomatosis in a woman with previous hysterectomy and bilateral salpingo-oophorectomy: A case report and review of the literature - Minhui L. Kim; Adriana Luk; Robert J. Cusimano; Narinder Paul; Jagdish Butany (Elsevier, 2014)
Intravenous leiomyomatosis (IVL) is a rare tumor, characterized by benign smooth muscle growth inside veins. The tumor arises from the uterine venous wall or uterine leiomyomas and is usually confined to the pelvic cavity. However, on rare instances, it may extend into the cardiac cavity (Pathol Annu 1988;23 Pt 2:153-158), and the pulmonary system (Arch Gynecol Obstet 2001;264:209-210). Treatment consists of surgical removal of the tumor, cessation of ovarian function and avoidance of estrogen replacement therapy (Gynecol Obstet Invest 2004;58:168-170). We present a case of intravenous leiomyomatosis with extension from IVC to RA, RV and PA, with an unusually rapid course of progression in the absence of estrogen (TAH-BSO, without concomitant hormonal therapy).